2013
DOI: 10.3989/ris.2011.04.11
|View full text |Cite
|
Sign up to set email alerts
|

Family influences in academic achievement. A study of the Canary Islands

Abstract: In this paper we study the family variables affecting academic achievement within a Canary Island sample. Parents' level of education, parents' expectations about academic achievement, Socioeconomic Status (SES), family size, type of family and parents' control over the student's homework are used as predicting variables in a logistic regression for predicting which variables load in high academic achievement. These variables are incorporated into two different theoretical models: the social capital view of Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 32 publications
1
9
0
5
Order By: Relevance
“…This circumstance may be influenced by the individual's socioeconomic context, but the family structure remains significant even after controlling for socioeconomic context. This result is consistent with Pérez et al (2013) using a different survey and methodology. Note also that a wide range of studies conclude that nonintact families (one-parent families, deceased parents, living with relatives other than parents, etc.)…”
Section: The Set Of Circumstances and Individual Incomesupporting
confidence: 90%
“…This circumstance may be influenced by the individual's socioeconomic context, but the family structure remains significant even after controlling for socioeconomic context. This result is consistent with Pérez et al (2013) using a different survey and methodology. Note also that a wide range of studies conclude that nonintact families (one-parent families, deceased parents, living with relatives other than parents, etc.)…”
Section: The Set Of Circumstances and Individual Incomesupporting
confidence: 90%
“…From an ecological framework, reciprocal positive interactions between these two key socializing spheres – families and schools – contribute positively to a child’s socioemotional and cognitive development (Bronfenbrenner, 1987). Empirical findings have demonstrated a positive association between parental involvement in education and academic achievement (Pérez Sánchez et al, 2013; Tárraga et al, 2017), improving children’s self-esteem and their academic performance (Garbacz et al, 2017) as well as school retention and attendance (Ross, 2016). Family involvement has also been found to be associated with positive school attachment on the part of children (Alcalay et al, 2005) as well as positive school climates (Cowan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lara and Saracostti [4] used cluster analysis to derive low, medium, and high level parental academic involvement categories and found that children who have parents with low involvement tend to have low academic achievement. Controlling for socioeconomic status and family size, parental education strongly predicted child academic achievement [58]. Perriel [59] found that children want and expect parent support of their academic pursuits and that parental involvement positively predicts child success at math and reading.…”
Section: Role Of Parent Academic Support In Child Academic Performmentioning
confidence: 99%